2015
DOI: 10.1007/s13762-015-0795-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of phytoplankton distribution for assessment of water quality in the Zhalong Wetland, China

Abstract: Phytoplankton community structures of water environmental were monitored from July to August 2010 in Zhalong Wetland in northeast China. Phytoplankton community was obtained from samples taken from 341 stations with different environmental conditions. Physicochemical parameters (chemical oxygen demand, the total nitrogen, the total phosphorus, chlorophyll a (Chl-a)) were measured simultaneously for comparison with phytoplankton samples. A total of 410 phytoplankton taxa belonging to 7 phyla, 9 classes, 20 orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Compared to single factors such as chemical factors, biomass or appear of indicator species, diversity indices are more integrated and relevant assessment approach with vital complete ecological information. Phytoplankton diversity indices were deemed to effective reflect the response of biotic matrices to environmental change in lakes or reservoirs ecosystem 21 , 48 . However, the application of phytoplankton diversity indices in trophic states assess of rivers is still weak.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to single factors such as chemical factors, biomass or appear of indicator species, diversity indices are more integrated and relevant assessment approach with vital complete ecological information. Phytoplankton diversity indices were deemed to effective reflect the response of biotic matrices to environmental change in lakes or reservoirs ecosystem 21 , 48 . However, the application of phytoplankton diversity indices in trophic states assess of rivers is still weak.…”
Section: Discussionmentioning
confidence: 99%
“…Biological diversity (H') and evenness (J) were used to analyze the community structure (Shannon and Weaver, 1949;Pielou, 1966). Based on Shannon-Wiener diversity index, results could be classified as oligotrophic (>3), β-mesotrophic (2-3), α-mesotrophic (1-2), and eutrophic (0-1) (Zhang and Zang, 2015).…”
Section: Pfgs Trophic State and Diversity Indicesmentioning
confidence: 99%
“…Phytoplankton diversity index has also been used to understand the variation of phytoplankton species throughout the year and the Shannon-Wiener Diversity Index (H') values of all stations were found between 1 and 2 in Lake İznik. Zhang and Zang (2015) indicated that values between 1-2 refer to α-mesotrophic conditions. H' and J indexes were lower in 2013 as a result of the more frequent bloom episodes.…”
Section: Trophic State and Ecological Statusmentioning
confidence: 99%
“…Phytoplankton, as primary producers in the wetland hydrosphere ecosystem, have rapid reproduction and are sensitive to environmental changes. The species composition abundance and the dominant species are important community structure characteristics and critical indicators reflecting water quality [ 1 , 2 ]. They are a critical component in determining the primary productivity of autotrophic water bodies and material cycling and energy flow [ 3 ]; for example, nutrient level, temperature, and light conditions have a strong influence on phytoplankton community structure [ 4 , 5 , 6 ], which is specifically manifested in their growth and reproduction rate.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the other water environment factors will also lead to changes in community structure of phytoplankton [ 13 ]; therefore, the temporal and spatial distribution pattern of phytoplankton can reflect the changes in wetland ecological conditions. Evaluating the characteristics of phytoplankton community structure is one of the crucial ways to explore the functions of wetland ecosystems [ 2 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%